Attitudes Toward Money and Control Strategies of Financial Behavior: A Comparison Between Overindebted and Non-overindebted Consumers - de Almeida, Filipa; Ferreira, Mário B.; Soro, Jerônimo C.; Silva, Carla Sofia (Frontiers in Psychology, 2021)
This paper addresses whether overindebted and non-overindebted consumers differ in their attitude towards money (i.e., financial accountability) and how it impacts consumers’ financial management behaviors. To this end, we used a) a simple attitude measure assessing financial accountability; and b) a cash flow management scale with three financial behavior categories: record keeping, adjusting balance and monitoring balance. Overindebted consumers were recruited via an NGO for consumer defense. Non-overindebted consumers were a convenience sample. As expected, although both groups showed high levels of financial accountability, non-overindebted consumers are more financially accountable than overindebted consumers. Both groups share similar financial management behaviors except for monitoring balance (e.g, monitoring spending to see if it is in line with what is expected), which was more frequent among non-overindebted consumers. Furthermore, a regression analysis indicates that financial accountability helps explain financial behavior differences between consumers above and beyond their indebtedness status. More financially accountable consumers have better financial behaviors, even when controlling for relevant socioeconomic variables. These findings point to the importance of attitudes regarding financial behaviors and may contribute to better interventions to reduce overindebtedness.